2020
DOI: 10.3390/jcm9072162
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Microbiota Dysbiosis in Patients with Non-Erosive Reflux Disease and Esophageal Adenocarcinoma

Abstract: Non-erosive reflux disease (NERD) and esophageal adenocarcinoma (EAC) are often regarded as bookends in the gastroesophageal reflux disease spectrum. However, there is limited clinical evidence to support this disease paradigm while the underlying mechanisms of disease progression remain unclear. In this study, we used 16S rRNA sequencing and mass-spectrometer-based proteomics to characterize the esophageal microbiota and host mucosa proteome, respectively. A total of 70 participants from four patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 59 publications
(66 reference statements)
5
44
1
Order By: Relevance
“…the relative abundance of Dorea, Bilophila, and Sulfurovum in the WB treatment was higher than that in the X and XO treatments. Dorea is a hydrogen producer (Zhou et al, 2020), Bilophila is a potential pathogen and detrimental bacteria (Toe et al, 2020), and Sulfurovum is related to sulfur metabolism (Mori et al, 2018). Furthermore, it has been reported that WB promoted steatosis and adipose tissue inflammation (Suriano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…the relative abundance of Dorea, Bilophila, and Sulfurovum in the WB treatment was higher than that in the X and XO treatments. Dorea is a hydrogen producer (Zhou et al, 2020), Bilophila is a potential pathogen and detrimental bacteria (Toe et al, 2020), and Sulfurovum is related to sulfur metabolism (Mori et al, 2018). Furthermore, it has been reported that WB promoted steatosis and adipose tissue inflammation (Suriano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the distal esophagus, the effect of PPIs may be more likely to be due to microbial related inflammatory changes, whereas previously attributed to direct acid contact mucosal injury. A study of patients with non-erosive reflux disease (NERD), erosive GERD, and BE compared PPI use vs no use within each respective group and found no change in α diversity or β diversity between PPI and non-PPI users of each group was reported, but composition of specific bacteria taxa at the phylum level was noted[ 53 ]. In particular, PPI use was associated with an increase in Firmicutes and Proteobacteria in BE, and a decrease in Bacteroidetes in NERD and reflux esophagitis (RE)[ 53 ].…”
Section: Normal Gastroesophageal Microfloramentioning
confidence: 99%
“…A study of patients with non-erosive reflux disease (NERD), erosive GERD, and BE compared PPI use vs no use within each respective group and found no change in α diversity or β diversity between PPI and non-PPI users of each group was reported, but composition of specific bacteria taxa at the phylum level was noted[ 53 ]. In particular, PPI use was associated with an increase in Firmicutes and Proteobacteria in BE, and a decrease in Bacteroidetes in NERD and reflux esophagitis (RE)[ 53 ]. In another study, biopsies taken before and after 8 wk of PPI treatment (lansoprazole 30 mg twice daily) revealed a significant decrease in the gram-negative Comamonadaceae spp.…”
Section: Normal Gastroesophageal Microfloramentioning
confidence: 99%
See 2 more Smart Citations